Residual stress measurement using NDT - Kawthaman, Mathnraj (2016)
Residual stresses in Titanium alloy can be simulated by welding Ti-6Al-4V with Tungsten Inert Gas welding (TIG). As a result, high residual stresses are introduced at the weld bead. Welding is chosen as it is one of the most common joining processes used in the aviation industry. This report presents the study of residual stresses present in a welded Ti-6Al-4V specimens. The sensitivity and accuracy of various Non-Destructive Testing (NDT) techniques of X-ray Diffraction (XRD) and Eddy Current on various heat treated welded Ti-6Al-4V specimens would be discussed. In this report, Surface roughness, Rockwell “C” Hardness, Visual Inspection, Eddy Current and X-ray Diffraction were conducted on Ti-6Al-4V specimens. The specimens will be undergo welding and different heat treatment process at the weld bead. These procedures will be done in Rolls Royce Labs. XRD and Eddy Current will then be conducted to determine the correlation between these two NDT techniques. This report will present the results obtained from Surface roughness, Rockwell “C’ Hardness, Visual Inspection, Eddy Current and XRD. The objective of the report is to determine the amount of residual stresses present in the heat treated welded specimens. Surface roughness would also be compared with Visual Inspection to determine correlations between them. The influence of Surface roughness on Eddy Current measurements was discussed. Attempts to correlate hardness number with XRD and correlation between Eddy Current and XRD would also be discussed. Future works could involve proposing residual stress introduced by grinding technique and other materials which have not been widely reported in the literature.